Modern histories of crime and punishment - Dubber, Markus Dirk; Farmer, Lindsay (Critical perspectives on crime and law, 2007)
Character, capacity, outcome : toward a framework for assessing the shifting pattern of criminal responsibility in modern English law / Nicola Lacey -- Criminal responsibility and the proof of guilt / Lindsay Farmer -- "An inducement to morbid minds" : politics and madness in the Victorian courtroom / Joel Peter Eigen -- The meaning of killing / Guyora Binder -- "An extraordinarily beautiful document" : Jefferson's bill for proportioning crimes and punishments and the challenge of Republican punishment / Markus D. Dubber -- The myth of private prosecution in England, 1790-1850 / Bruce P. Smith -- Hans Litten and the politics of criminal law in the Weimar Republic / Benjamin Hett -- Civilizing Darwin : Holmes on criminal law / Gerry Leonard -- Bodies, words, identities : the moving targets of the criminal law / Mariana Valverde -- Criminal law at a fault line of imperial authority : inter-racial homicide trials in British India / Martin Wiener -- Crime and punishment on the tea plantations of colonial India / Elizabeth Kolsky -- "Enfeebling the arm of justice" : perjury and prevarication in British India / Wendie Ellen Schneider